Urban resilience assessment from the perspective of cross-media carbon metabolism - Qiao, Dan; Shen, Shuo; Chen, Jiaxuan; Lu, Weiwei; Xu, Chao; Su, Meirong (Journal of cleaner production, 2024)
With the accelerating pace of globalization, uncertainty and unknown risks within open and complex urban systems increase with the occurrence of problems such as the conflict between humans and natural land use, water scarcity, and the continuing loss of biodiversity. Thus, the improvement of urban resilience has emerged as an important issue in the context of global urbanization. However, a knowledge gap remains in its evaluation from the perspective of systematic resource/element metabolic processes. To understand the urban resilience response mechanism better and depict metabolic processes systematically, an urban resilience assessment framework of “robustness-adaptability-restorability-coordination” based on the cross-media carbon metabolism network model was established. Principles of material flow analysis and ecological network analysis were applied to examine the urban resilience of Guangzhou, China, from 2010 to 2020. Results showed the urban resilience level decreased from a carbon metabolism perspective during the study period. This was reflected in an overall decline in system robustness and restorability, relatively unchanged adaptability, and a non-beneficial coordination relationship. Recommendations such as regulating key sectors (e.g., agriculture and construction) were proposed to improve urban resilience. This research will bring a new insight into future urban resilience assessment and contribute the urban sustainable development.